Assembly of yolk spindles in the early Drosophila embryo. - Riparbelli, M.G.; Callaini, G. (Mechanisms of Development, 2003)
The development of the early Drosophila embryo is marked by the separation of two nuclear lineages, yolk and somatic nuclei, each having its own division program despite residing in a common cytoplasm. We show that the failure of nuclear division of the yolk nuclei is a consequence of dysfunction in bipolar spindle organization during mitosis 10 and 11. Yolk spindle organization defects are directly correlated to centrosome behaviour, which is abnormal in at least three sequential aspects. First, the yolk centrosomes do not migrate properly along the nuclear envelope during nuclear cycles 10 and 11 and give rise to non-functional monopolar spindles. Second, the centrosomes detached from the poles spindle at the end of nuclear cycle 11, leaving the spindles anastral. Third, the free centrosomes duplicate in the absence of nuclear division during last mitoses and early gastrulation, but do not separate properly. In spite of their reduced nucleating properties, beyond the nuclear cycle 12, the yolk centrosomes contain typical centrosomal antigens, suggesting that their structural organization has not been changed after they disperse in the cytoplasm. Our findings also demonstrate that the centrosome dynamics are spatially and temporally regulated in the yolk region. This observation is consistent with the presence of rate-limiting levels of maternally provided key molecular components, needed for centrosome duplication and positioning. The presence of normal and abnormal centrosomes in the same cytoplasm provides an useful model for investigating the common regulators of the nucleus and centrosome cycle which ensure precise spindle pole duplication.